ChatGPT: The Future Research Assistant or an Academic Fraud? [A Case Study on a State University Located in Jakarta, Indonesia] - Rahardyan, Tri Marhendra; Susilo, Candra Hapsari; Iswara, Alifia Malikha Nur; Hartono, Meinar Lutfiah (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
ChatGPT is an artificial intelligence (AI) technology currently popular among the public. This groundbreaking technological development has reached various fields, including education, where ChatGPT can facilitate learning activities, making them more effective and efficient. However, this development can also be misused and may facilitate academic fraud. This paper aims to understand the benefits and threats of using ChatGPT for educational purposes and its potential misuse for academic fraud. This study involves a literature review of published journals containing pertinent scientific articles and utilizes data processed from questionnaires distributed to students at a university in Jakarta. Our analysis shows that ChatGPT is useful in several ways, including providing ideas and frameworks for researchers, supporting access to various types of literature, constructing abstracts, formulating research questions and hypotheses, and detecting grammatical errors. In contrast, significant risks are associated with using ChatGPT, particularly in research. These risks include plagiarism, ethical concerns, integrity issues, and the potential inaccuracy of data generated by ChatGPT. Therefore, further validation is needed. Consequently, our analysis also indicates that using ChatGPT to write scientific articles or for closed-book exams is considered academic dishonesty.